Antioxidant Effect of 0.2% Xanthan Gum in Ocular Surface Corneal Epithelial Cells. (January 2015) - Amico, Carla; Tornetta, Tatiana; Scifo, Christian; Blanco, Anna Rita
Abstract Purpose: Oxidative damage and inflammation are expected to be involved in age-related functional decline of lachrymal gland, that induces lachrymal dysfunction; this resulting in dry eye disease. Therefore, we investigated the potential antioxidant effect of 0.2% xanthan gum (XNT) in human corneal epithelial cells (HCE), in comparison with other widely used tear substitute polymers, such as 0.2% hydroxyethylcellulose (HEC), 0.2% hyaluronic acid (HA) and 0.5% carboxymethylcellulose (CMC). Methods: Subconfluent (80%) HCE (Human Corneal Epithelial) cultures were treated with the different polysaccharides at the above reported concentrations. The effect of every polymer was investigated with and without 0.5 mM H2O2 In detail, hydrogen peroxide was added 1 hour after the addition of polysaccharides. Twelve hours later, reactive oxygen species (ROS) production (dichlorofluorescein diacetate spectrofluorimetric test) was assessed and their values were normalized versus protein content. Morphological analysis was performed by optical microscopy. Results: No morphological differences in HCE compared to control cells (CTRL, cells treated with the buffer used for polymer solubilization) were observed in any of the tested polymers, whereas, in the presence of 0.5 mM H2O2 HCE clearly showed signs of cytotoxicity. Polymers did protect cultures from oxidative stress with XNT>HA = HEC>CMC, as evidenced by microscopic analysis. These results were confirmed from ROS measurements, which showed XNT as the only polysaccharide to restore the levels of ROS comparable to CTRL, in presence of H2O2. Conclusions: 0.2% xanthan gum was able to protect HCE by oxidative stress, bringing the ROS level down to CTRL values. Considering that in dry eye syndrome oxidative stress sustains inflammation and apoptotic cell death, the use of xanthan gum in ophthalmic preparations could be beneficial.